Irradiation-induced β to α SiC transformation at low temperature - Chad M. Parish (Nature Portfolio, 2017)
Abstract We observed that β-SiC, neutron irradiated to 9 dpa (displacements per atom) at ≈1440 °C, began transforming to α-SiC, with radiation-induced Frank dislocation loops serving as the apparent nucleation sites. 1440 °C is a far lower temperature than usual β → α phase transformations in SiC. SiC is considered for applications in advanced nuclear systems, as well as for electronic or spintronic applications requiring ion irradiation processing. β-SiC, preferred for nuclear applications, is metastable and undergoes a phase transformation at high temperatures (typically 2000 °C and above). Nuclear reactor concepts are not expected to reach the very high temperatures for thermal transformation. However, our results indicate incipient β → α phase transformation, in the form of small (~5–10 nm) pockets of α-SiC forming in the β matrix. In service transformation could degrade structural stability and fuel integrity for SiC-based materials operated in this regime. However, engineering this transformation deliberately using ion irradiation could enable new electronic applications.